Measurement of J/psi production in pp collisions at sqrt(s)=7 TeV - Collaboration, L; Aaij, R; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Cartelle, P; Jr, A; et al. (2011)
The production of J/psi mesons in proton-proton collisions at sqrt(s)=7 TeV is studied with the LHCb detector at the LHC. The differential cross-section for prompt J/psi production is measured as a function of the J/psi transverse momentum pT and rapidity y in the fiducial region 0